2013
DOI: 10.1007/s10719-013-9495-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of class I and II α-mannosidases from Drosophila melanogaster

Abstract: Homology searches indicated that up to five class I α-mannosidases (glycohydrolase family 47) and eight class II α-mannosidases (glycohydrolase family 38) are encoded by the fruitfly (Drosophila melanogaster) genome. Selected example mannosidases were expressed in secreted form using the yeast Pichia pastoris. A number of characteristics of these enzymes were determined with p-nitrophenyl-α-mannoside as substrate; particularly striking were the low optima (pH 5) of three class II mannosidases most closely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…This splicing pattern was conserved in Drosophila. 23,31,32 At present it is not clear if the 2, only marginally different protein isoforms, have distinct catalytic activities, but they appear to be always co-expressed. AmLAM is ubiquitous, but shows markedly variable levels throughout development and in various tissues.…”
Section: Identification Of Multiple Allelic Variants Of Amlammentioning
confidence: 99%
“…This splicing pattern was conserved in Drosophila. 23,31,32 At present it is not clear if the 2, only marginally different protein isoforms, have distinct catalytic activities, but they appear to be always co-expressed. AmLAM is ubiquitous, but shows markedly variable levels throughout development and in various tissues.…”
Section: Identification Of Multiple Allelic Variants Of Amlammentioning
confidence: 99%
“…31 13 The supernatants of yeast expressing soluble forms of the α-mannosidase were incubated with the substrate pNP-Manp at 37°C for 2-3 h. The standard assay mixture consisted of 50 mM sodium acetate buffer (pH 4.5 for JBMan, pH 5.2 for dLManII or pH 5.8 for dGMIIb), 2 mM pNP-Manp (from 100 mM stock solution in DMSO), 1-5 μL enzyme (supernatant of the culture medium) and in case of dGMIIb final 0.2 mM CoCl2 in a total reaction volume of 50 μL. A blank sample contained no enzyme.…”
Section: Biochemistrymentioning
confidence: 99%
“…31,32 The tested compounds 5, 14, 15, 22, 26, 27, 30, 35 and 36 were prepared as stock solutions in DMSO (100 mM) and data were obtained in triplicate over a concentration range of 1-5 mM. Jack bean α-mannosidase (5μL) was pre-incubated for 5 min at 20°C with the inhibitor under evaluation.…”
Section: Biochemistrymentioning
confidence: 99%
“…These enzymes are classed into a number of different subfamilies based on their localisation, biochemical properties and substrate specificities; they include lysosomal α-mannosidase, likely to have a role in scavenging degraded glycoproteins, the cytosolic α-mannosidase and the well-characterised Golgi α-mannosidase (Henrissat & Bairoch, 1993; Nemcovicova et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…It is localised within the lysosome, typically has a pH optimum of 4.0–4.5, is activated by Zn 2+ , and has a broad substrate specificity, hydrolysing at α1,2, α1,3 and α1,6 linkages during catabolism (Daniel, Winchester & Warren, 1994; Gonzalez & Jordan, 2000; Henrissat & Bairoch, 1993; Nemcovicova et al, 2013). Structural characterisation of this enzyme in Bos taurus (cattle) and Drosophila melanogaster (vinegar fly) has shown that LAM is proteolytically cleaved into five peptides (A–E), with peptides A and B forming the active-site domain.…”
Section: Introductionmentioning
confidence: 99%